Calcined Nickel‐Cobalt Mixed Metal Phosphonate with Efficient Electrocatalytic Activity for Oxygen Evolution Reaction. Issue 2 (16th January 2018) - Feng, Pingjing; Cheng, Xian; Li, Jintang; Luo, Xuetao
Abstract: Transition metal phosphonates have recently gained attentions as efficient catalysts for oxygen evolution reaction (OER). In this paper, flower‐like nickel‐cobalt phenylphosphonate microspheres were sythesized, which could be used as excellent electrocatalyst for OER. After calcined at high temperature in air, resulted product of metal pyrophosphate exhibited outstanding electrocatalytic property. A small amount of carbon coming from the pyrolysis of phenylphosphonate were doped in matrix of metal pyrophosphonate, which promoted the OER catalysis by improving the electron transfer of material. Sample denoted as CoNiPP‐600 had the most excellent catalytic activity, with a current density of 10 mA/cm 2 at a lower over‐potential of 264 mV, Tafel slope of 60 mV⋅dec −1 and superior durability in 1.0 M KOH solution. Abstract : The flower‐like nickel‐cobalt phenylphosphonate microspheres and their calcined derivatives were sythesized, which possessed excellent electrocatalyst for OER. Sample denoted as CoNiPP‐600 had the most excellent catalytic activity, with a current density of 10 mA/cm 2 at a lower over‐potential of 264 mV, Tafel slope of 60 mV⋅dec −1 and superior durability in 1.0 M KOH solution